Real-time information presentation system for support during breast reconstruction - Washio, Toshikatsu; Kaneko, Kotaro; Chiba, Shinji; Yano, Tomoyuki; Suzuki, Takashi; Arafune, Tatsuhiko (Transactions of Japanese Society for Medical and Biological Engineering, 2020)
Reduction of the moldability of the postoperative breast shape during breast reconstruction has been cited as an issue. We have developed a system that obtains three-dimensional shape difference information before mastectomy and during reconstruction, and maps the local shape difference information to the patient's skin superficial. The system evaluation by a plastic surgeon using this system revealed that it was desirable to be able to grasp shape information more quickly. Therefore, the purpose of this study was to develop a system that calculates the shape difference information in real time based on the left and right breast shapes. As a system evaluation, the shape difference during reconstruction was reproduced using a mannequin simulating a patient, and measurement and projection experiments were performed. It is now possible to project the shape difference information onto the skin surface without the process of pasting the shape difference texture onto the three-dimensional shape data.